Knowing Educational Psychology: A Tool to Smoothen the Teaching-Learning Process - Karim, Md Ataul (Green University Review of Social Sciences, 2022)
When the idea of an efficient teacher comes in our mind, the first thing that we consider as the prominent issue is whether that person has proper knowledge of the subject that s/he is going to teach. The secondary concern surfaces whether that person is knowledgeable enough to present the subject matter. Now, one question that most of us never think about or simply ignore is: Are all these qualities enough to be a successful teacher? Who is going to answer this question? Who is going to judge whether a teacher is ‘perfect’ or not? Will the judge be another senior teacher or a prominent educationist in that field or the students who always closely observe the activities of the teacher? Some people may raise the objection saying how students can judge the teacher as they are not mature enough for having lack of knowledge and sufficient experiences of life beyond the classroom. To tackle such questions, one great source of help is to know theories and practices of educational psychology in depth as it fundamentally challenges the notion of considering the students as machines that run with different types of programs. It strongly asserts that the students are not machines, they are human beings with frequently changing characteristics, emotions, desires, moods, responses/reactions and so on. So, one of the objectives of this paper is to show how, by understanding the psychology of the students, a teacher can provide them proper guidance. Also, this paper aims at finding out different important issues/concerns by exploring and contextualizing various prominent psychological theories of education to create an overall positive as well as enabling educational environment both for the teacher and the learners. To attain this end, this paper uses insights from educational psychology in particular to keep the frame of discussion focused and manageable. Green University Review of Social Sciences Dec 2021; 7(1-2): 165-174